Literature Review of Tax Audits: Reflections on the Minister of Finance Regulation Number 15 of 2025 Concerning Tax Audits - Riantari Maharani; Biizni Putri Bengi; Chairanisa Natasha Miraza; Muhammad Ichsan Adnan; Imam Gunanjar (STMIK Indonesia Banda Aceh, 2025)
Tax audits are an important tool in efforts to improve taxpayer compliance and optimize state revenue. In line with technological advancements and the increasing complexity of economic transactions, the Directorate General of Taxes has undergone a digital transformation through the implementation of the Coretax Administration System, which encourages the renewal of tax audit administration. This study aims to analyze the implementation of Minister of Finance Regulation Number 15 of 2025 on Tax Audits, which brings reforms in audit governance, including regulatory simplification, audit classification, transparency through Terms of Reference, and the digitization of audit document submission. This study employs a descriptive literature review method, drawing from relevant regulations and literature in the field of taxation. The results of the study indicate that the implementation of this regulation has been able to streamline the audit process, increase legal certainty, and contribute to tax education for taxpayers through audits that utilize databases. This reform is expected to strengthen a fair, transparent, and accountable national tax system and encourage voluntary compliance by taxpayers to support national development.